(untitled) (New York, NY, USA, 1993)
The study of carbon has been revolutionized since the discovery of the soccerball shaped C60 molecule Buckminsterfullerene. This book examines the modern study of the chemistry, physics and astrophysics of carbon, through contributions from leading workers in the subject. It includes a history of the origins of a soccerball structure for the C60 molecule and a section on its discovery and production. It then looks at the theory and the astrophysics and chemistry of the material. These contributions result from a meeting held at the Royal Society in October 1992. The contributions formerly appeared in the Philosophical Transactions of the Royal Society
Keywords: Fullerenes,Hóa vô cơ; Congresses